Digitalization and Spiritual Transformation: A Phenemenological Study of Young Catholic Priest in Diocese of Palangka Raya - Manik, Resmin; Jimmy, Andreas (International Journal of Artificial Intelligence Research, 2025)
This research explores the phenomenological experiences of young Catholic priests in the Diocese of Palangkaraya in constructing their spirituality amid digital transformation and the cultural expectations of the Dayak community. Using a mixed-methods sequential explanatory design with Interpretative Phenomenological Analysis (IPA) involving 10 priests aged 30-40 years with 1-10 years of ordination, the research revealsfourmainthemes:thedualityofdigitalexperienceinspirituality, negotiationoftensionbetweentraditionandmodernity,reconstructionof priestlyidentity,andspiritualadaptationstrategies.Quantitativeanalysis shows significant correlations between digital competence (r=0.68, p<0.01) and cultural intelligence (r=0.72, p<0.01) with digital pastoral adaptation. Qualitative findings reveal that young priests experience "cultural-digital dissonance" between demands for physical presence in Dayakritualsanddigitalefficiency,aswellas"erosionofsilence"dueto continuous connectivity. In response, they develop a "trihybrid spirituality"thatintegratesCatholictradition,Dayakwisdom,anddigital technologythroughstrategiesofscheduleddigitallimitations,theological reinterpretation, and ritual hybridization. This research contributes to understandingspiritualtransformationinthedigitalerawithinindigenous contexts and offers practical implications for reformulating priestly formation and developing inculturation models that integrate digital dimensions without neglecting local wisdom.